2019
DOI: 10.9755/ejfa.2019.v31.i4.1936
|View full text |Cite
|
Sign up to set email alerts
|

Influence of delayed cooling on quality of bell pepper (Capsicum annuum L.) stored in a controlled chamber

Abstract: Improper postharvest handling, including delaying cooling, is a big concern for maintaining the freshness of fruit and vegetables in the postharvest supply chain. The objective of this study was to investigate the influence of short delays in cooling on some important quality parameters such as physiological weight loss, firmness, total soluble solids (TSS), and color (L*, h°, and C*) values of bell peppers stored in a controlled chamber. Bell peppers treated with three different treatments showed a gradual ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…In this study, FOLO rapidly reduced weight loss as compared to FXLX samples at the end of the storage period (Figure 2A,B), confirming the efficacy of forced-air precooling and PE liner treatments on bell pepper fruit quality during shipment and storage. This result corroborated with Kabir et al [30], who observed a reduced weight loss (1.46 wt.%) in bell peppers when precooled and immediately stored in a controlled chamber. The increased weight loss of FXLX might be due to changes in the permeability of cell membranes that made them more sensitive to water loss [31] since the fruits were not precooled and wrapped in PE liners during storage.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, FOLO rapidly reduced weight loss as compared to FXLX samples at the end of the storage period (Figure 2A,B), confirming the efficacy of forced-air precooling and PE liner treatments on bell pepper fruit quality during shipment and storage. This result corroborated with Kabir et al [30], who observed a reduced weight loss (1.46 wt.%) in bell peppers when precooled and immediately stored in a controlled chamber. The increased weight loss of FXLX might be due to changes in the permeability of cell membranes that made them more sensitive to water loss [31] since the fruits were not precooled and wrapped in PE liners during storage.…”
Section: Discussionsupporting
confidence: 91%